On-chip generation of microbubbles in photoacoustic contrast agents for dual modal ultrasound/photoacoustic in vivo animal imaging - Das, Dhiman (2018)
Dual-modal photoacoustic (PA) and ultrasound (US) contrast agents are becoming increasingly popular in recent years. Here, a flow-focusing junction based microfluidic device is used for the generation of nitrogen microbubbles (<7 μm) in two photoacoustic contrast agents: methylene blue (MB) and black ink (BI). The microbubble diameter and production rate could be precisely controlled in both MB and BI solutions. Microbubbles were collected from the outlet of the microfluidic device and optical microscope was used to study the size distributions in both solutions. Next, the microbubbles in both solutions were injected into tubes for phantom imaging experiments. Signal to noise ratio (SNR) of both US, PA imaging experiments were calculated to be 51 dB, 58 dB in MB + microbubbles and 56 dB, 61 dB in BI + microbubbles, respectively. Finally, the microbubbles were injected into the urinary bladder of rats for in vivo animal imaging. The SNR in US imaging with MB + microbubbles and BI + microbubbles were 41 dB and 48 dB, respectively. Similarly, the SNR in PA imaging with the same solutions were 32 dB and 36 dB, respectively. The effect of size and concentration of microbubbles in both MB and BI solutions, on the US and PA signals, has been examined.